2014
DOI: 10.4161/cbt.28553
|View full text |Cite
|
Sign up to set email alerts
|

PDE5 inhibitors enhance the lethality of standard of care chemotherapy in pediatric CNS tumor cells

Abstract: We determined whether clinically relevant phosphodiesterase 5 (PDE5) inhibitors interacted with clinically relevant chemotherapies to kill medulloblastoma cells. In medulloblastoma cells PDE5 inhibitors interacted in a greater than additive fashion with vincristine/etoposide/cisplatin to cause cell death. Knockdown of PDE5 expression recapitulated the combination effects of PDE5 inhibitor drugs with chemotherapy drugs. Expression of dominant negative caspase 9 did not significantly inhibit chemotherapy lethali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
1
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 26 publications
0
55
1
1
Order By: Relevance
“…PDE5 inhibitors enhanced and prolonged the induction of DNA damage as judged by Comet assays along with histone H2AX and checkpoint kinase-2 (CHK2) phosphorylation. Sildenafil was also found to interact with multiple standard of care chemotherapeutic agents (vincristine, etoposide, and cisplatin) in an additive fashion to kill medulloblastoma cells by induction of DNA damage in a NO synthase-dependent pathway (Roberts et al, 2014). These results suggested that sildenafil enhances chemotherapeutic efficacy through both death receptor and mitochondrial signaling as part of the combinatorial killing process.…”
Section: Pde5 Inhibitors In Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…PDE5 inhibitors enhanced and prolonged the induction of DNA damage as judged by Comet assays along with histone H2AX and checkpoint kinase-2 (CHK2) phosphorylation. Sildenafil was also found to interact with multiple standard of care chemotherapeutic agents (vincristine, etoposide, and cisplatin) in an additive fashion to kill medulloblastoma cells by induction of DNA damage in a NO synthase-dependent pathway (Roberts et al, 2014). These results suggested that sildenafil enhances chemotherapeutic efficacy through both death receptor and mitochondrial signaling as part of the combinatorial killing process.…”
Section: Pde5 Inhibitors In Cancermentioning
confidence: 99%
“…In recent years, there has been tremendous interest in identifying new clinical uses of PDE5 inhibitors in various ailments including cardiovascular disease (Kukreja et al, 2004; Kukreja et al, 2005; Kukreja et al, 2011), diabetes (Giannetta et al, 2012; Koka et al, 2012; Koka et al, 2013; Koka et al, 2014; Varma et al, 2012) and cancer (Black et al, 2008; Booth et al, 2014a; Booth et al, 2014c; Booth et al, 2014b; Das et al, 2010; Hamilton et al, 2013; Resnick et al, 2009; Roberts et al, 2014). Today, close to 100 clinical trials (http://www.clinicaltrials.gov) with PDE5 inhibitors focusing on the potential cardiovascular benefits have been completed or are ongoing.…”
Section: Introductionmentioning
confidence: 99%
“…In small cell lung cancer, autophagy appeared to protect against both cisplatin and etoposide cytotoxicity 42 while in leukemic cells, the opposite outcome was observed in that activation of autophagy increased sensitivity to both etoposide and adriamycin 43 . In several medulloblastoma cell lines, the combination of etoposide and sildenafil (utilized as a potential sensitizer to chemotherapy) resulted in different functions of autophagy in a cell line-dependent manner 44 . siRNA-mediated silencing of ATG5 and Beclin-1 resulted in increased sensitization (by trypan blue exclusion) of HOSS1 cells to the etoposide/sildenafil combination while it decreased sensitivity to the same combination in DAOY and D283 cell lines.…”
Section: Chemotherapy-induced Autophagymentioning
confidence: 99%
“…Then, they co-treated cells with L-NAME and found out that NOS inhibition accompanying PDE5 inhibitors suppressed cell killing. Most probably NO/NOS has a role in killing of medulloblastoma cells [81]. A study done in knockout mice exhibited that iNOS has an important role in medulloblastoma formation.…”
Section: Roles Of Noss In Brain Cancersmentioning
confidence: 99%